Odpowiedzi

2009-11-05T20:21:04+01:00
X^+9-2x+10-4=-2x+x^+15
9a^+25+4a-28+2a-10=9a^+6a-13
x^+1-x^+4-4x-3=-4x+2
2a^-8^-3a^+15^-4a+4= 2a^+64-3a^+225-4a+4= 3a+293
2x^+49+x^-25-x^+2x-2x-4=2x^+20
6x^-3^-2x^+2^-x^+x-x-1=3x^-9+4-1=3x^-6
Najlepsza Odpowiedź!
2009-11-05T20:28:12+01:00
^ - to są do potęgi 2??

jak tak to będzie tak:

(x+3)²-2(x-5)-4=x²+6x+9-2x+10-4=x²+4x+19

(9a-5)²+4(a-7)+2a-10 = 81a²-90a+25+4a-28+2a-10=81a²-84a-3

(x+1)²-(x-2)²-4x-3=x²+2x+1-x²-4x+4-4x-3=-6x+5

2(a-4)²-3(a+5)²-4(a-1)=2a²-16a+32-3a²-30a-75-4a²+8a-4=-5a²-38a-47

(2x+7)²+(x-5)²-(x-2)(x+2)=4x²+28x+49+x²-10x-1-x²+4=4x²+18x+52

3(2x-1)²-2(x-2)²-(x-1)(x+1)=12x²-12x+3-2x²+8x-8-x²+1=9x² -4x-4